The Role of Vlog Assignments In Developing Pragmatic Skills Among Students at University Level - Ramadhani, Tria Rahayu; Anisah, Rifqoh Nu’ma; Fathr, Abdu Dzulhaq Laqod (Jurnal Simki Postgraduate, 2024)
Effective speaking involves not only linguistic competence but also pragmatic skills, which are often overlooked in traditional language instruction. While previous studies on vlogs in language learning have primarily examined linguistic aspects, the role of pragmatic competence remains underexplored. This study addresses this gap by investigating the impact of vlog-making assignments on pragmatic skill development among English as a Foreign Language (EFL) students, utilizing Speech Act Theory as the theoretical framework. Employing a qualitative descriptive approach, the research analyzed vlogs from five students. The findings revealed that students predominantly used Representatives and Expressives, demonstrating their capacity to convey contextually appropriate observations, opinions, and emotions. These results highlight the potential of vlog-making assignments in enhancing both linguistic and pragmatic communication skills. The study's limitations, notably the small sample size and qualitative design, underscore the need for expanded research with more diverse samples to comprehensively understand how vlog assignments influence pragmatic skill development. Despite these constraints, the research advocates for integrating digital tools in language education and emphasizes the importance of assessment methods that holistically evaluate linguistic and pragmatic competencies.